PROBLEMS AND PROSPECTS OF TAXATION OF SMALL BUSINESS IN UZBEKISTAN - Tursunova Nigora Khusnidinovna; Tashkent State Technical University (Research Parks Publishers, 2020)
The article deals with the role of taxation for small businesses. It analyzes the main trends in the development of small business in Uzbekistan. The analysis of the economic indicators of activity of small enterprises, their share in the GDP of the state. The main forms of taxation of small businesses, especially the use of the simplified taxation system. Conclusions about future tax regulation of small business. The measures relating to the further improvement of tax policy and tax system of Uzbekistan.